Future development of peace education in Bali: Lessons from a critical analysis of the peace education curricula of Hiroshima - Nitiasih, Putu Kerti; Mahayanti, Ni Wayan Surya; Jampel, I Nyoman; Asril, Nice Maylani; Budhyani, I Dewa Ayu Made; Nakaya, Ayami (Edelweiss Applied Science and Technology, 2025)
This study explores the necessity of promoting peace education in Bali through a critical analysis of the peace education curricula in Hiroshima, identifying lessons that can enhance Bali's efforts in fostering harmony and conflict resolution. By investigating the ideologies, power structures, and socio-political settings influencing Hiroshima's framework, the research employs qualitative methods, including expert interviews and detailed curriculum analysis, to examine its effectiveness and inclusiveness. The findings reveal that Hiroshima's peace education is deeply rooted in its historical trauma, emphasizing anti-war narratives and collective harmony, but it faces challenges in integrating multicultural perspectives and addressing environmental peace. For Bali, the study highlights the potential of incorporating local philosophies like Tri Hita Karana to create a culturally resonant framework that balances global and local issues, fostering inclusivity, sustainability, and social justice. The implications suggest that a localized, participatory, and environmentally integrated approach to peace education can empower students and communities in Bali to actively contribute to a more peaceful and equitable society.